ANALISIS PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH DAN AZARINE DI KALANGAN MAHASISWA - Sinta lidia sari; Fima fatihatul makiyah; Syamsul hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to examine and analyze price perceptions of purchasing decisions for Wardah and Azarine products among students. This research uses quantitative methods. The data used is primary data obtained through a questionnaire distributed via Google Form. The sampling method used non-probability sampling with purposive sampling technique, with a research sample of 183 respondents. The test stages carried out were validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression. The testing tool used was IBM SPSS 26. The research results showed that price perception had a significant influence on purchasing decisions for Wardah and Azarine products.